Imagining the Alpha male of the tourism tribe. Issue 4 (2nd October 2017) - Ek, Richard; Larson, Mia
Abstract: This paper analyses how the "alpha male" of the tourism academy tribe is imagined in celebratory contexts. The tradition is interesting from a gender perspective, in that the majority of celebratory portraits found in tourism research journals are those of male scholars. Whether this is regarded as a coincidence or a consequence of the resilience of a glass ceiling, it is interesting to investigate how these "alpha males" and their academic lifeworks are described, characterized, and presented. The paper contains a quantitative description and qualitative analysis of the portraits published in Anatolia. In particular, we apply philosopher Stephen Pepper's root metaphors of formism, organicism, mechanism, contextualism to examine how tourism research work in the world is imagined.